(untitled) (Research, Society and Development, 2022)
Objective: to map the flowchart evidence on depression for adolescents in the school context. Method: Scope Review protocol produced from the recommendations of the Joanna Briggs Institute manual using the PRISMA-ScR checklist extension, in the following information sources: Web of Science, National Library of Medicine; Latin American and Caribbean Literature on Health Sciences, Virtual Health Library, Pubmed, Pepsic and Scielo. Search will also be carried out on websites of the Ministry of Health, World Health Organization, Brazilian Society of Psychiatry, Brazilian Association of Mental Health, Federal Council of Psychology, Google Scholar and books that are related to the theme. Studies that answer the research question, published in any language, will be considered eligible. The Review will take place independently from the Rayyan software performed by two reviewers. The results will be presented in the form of tables, charts, illustrations and a narrative summary.